Prognostic significance of thrombocytosis in lung cancer: a systematic review and meta-analysis. (3rd October 2021) - Ma, Yunfei; Li, Guangda; Yu, Mingwei; Sun, Xu; Nian, Jiayun; Gao, Yu; Li, Xiaoxiao; Ding, Tongjing; Wang, Xiaomin
Abstract: A potential relationship between poor prognosis and thrombocytosis has been suggested by previous studies in lung cancer, but the conclusions continued to be controversial. Here, we performed a meta-analysis to explore the prognostic impact of thrombocytosis in lung cancer. The Cochrane Library, EMBASE and PubMed databases were comprehensively and systematically retrieved from establishment to May 5, 2020. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were applied to evaluate overall effects. Heterogeneity was assessed using I 2 statistics and Cochran's Q test. Sensitivity and subgroup analyses were performed to analyze the sources of heterogeneity. Publication bias was examined using the Egger's test and pooled HR was regulated using the trim-and-fill approach when publication bias was observed. A total of 37 studies including 14, 833 patients were enrolled in the meta-analysis. Thrombocytosis was significantly correlated to poor overall survival (HR 1.033; 95% CI 1.017–1.050), disease-free survival (HR 1.568; 95% CI 1.276–1.928), and progression-free survival (HR 1.653; 95% CI 1.069–2.556). Although publication bias was identified, rectification for this bias using the trim-and-fill approach did not change the combined HR substantially. In conclusion, this meta-analysis result suggested that thrombocytosis is a predictor of poor prognosis in lung cancer.